Predictors of Residual Viraemia in Patients on Long-Term Suppressive Antiretroviral Therapy. Issue 1 (January 2013) - Zheng, Lu; Bosch, Ronald J; Chan, Ellen S; Read, Sarah; Kearney, Mary; Margolis, David M; Mellors, John W; Eron, Joseph J; Gandhi, Rajesh T; ,
Background: HIV-1-infected individuals with plasma RNA<50 copies/ml on antiretroviral therapy (ART) may have residual, low-level viraemia detectable by PCR assays that are able to detect a single copy of viral RNA (single-copy assay [SCA]). The clinical predictors of residual viraemia in patients on long-term suppressive ART are not yet fully understood. Methods: We evaluated factors associated with residual viraemia in patients on suppressive ART who underwent screening for a raltegravir intensification trial (ACTG A5244). The screened population was HIV-1-infected adults receiving ART for ≥12 months with pre-ART HIV-1 RNA>100, 000 copies/ml and on-therapy RNA levels below detection limits of commercial assays for ≥6 months. Results: Of 103 patients eligible for analysis, the median age was 46 years and the median duration of viral suppression was 4.8 years. 62% had detectable viraemia (>0.2 copies/ml) by SCA (median 0.2 copies/ml, IQR <0.2–1.8). Younger patients had lower HIV-1 RNA levels than older individuals (r=0.27, P =0.005). Patients with virological suppression on ART for 2 years or less had higher residual viraemia than those with suppression for >2 years (median 2.3 versus 0.2 copies/ml; P =0.016). Conclusions: Among HIV-1-infected patients with pre-ART HIV-1 RNA>100, 000 copies/ml, residual viraemia was detectable in the majority (62%) despite many years of suppressive ART. Higher level viraemia was associated with older age and <2 years of virological suppression on ART. These findings should help in the selection of candidates for clinical trials of interventions designed to eliminate residual viraemia.